Combination Therapy With Charged Particles and Molecular Targeting: A Promising Avenue to Overcome Radioresistance - Konings, Katrien; Vandevoorde, Charlot; Baselet, Bjorn; Baatout, Sarah; Moreels, Marjan (Frontiers in Oncology, 2020)
Radiotherapy plays a central role in the treatment of cancer patients. Over the past decades, remarkable technological progress has been made in the field of conventional radiotherapy. In addition, the use of charged particles (e.g., protons and carbon ions) makes it possible to further improve dose deposition to the tumor, while sparing the surrounding healthy tissues. Despite these improvements, radioresistance and tumor recurrence are still observed. Although the mechanisms underlying resistance to conventional radiotherapy are well-studied, scientific evidence on the impact of charged particle therapy on cancer cell radioresistance is restricted. The purpose of this review is to discuss the potential role that charged particles could play to overcome radioresistance. This review will focus on hypoxia, cancer stem cells, and specific signaling pathways of EGFR, NFκB, and Hedgehog as well as DNA damage signaling involving PARP, as mechanisms of radioresistance for which pharmacological targets have been identified. Finally, new lines of future research will be proposed, with a focus on novel molecular inhibitors that could be used in combination with charged particle therapy as a novel treatment option for radioresistant tumors.